OAT RESISTANCE TO LOOSE SMUT AND RED-BROWN LEAF SPOT UNDER NATURAL DISEASE DEVELOPMENT CONDITIONS IN THE NORTH OF THE RUSSIAN FEDERATION - A. D. Kabachov; V. A. Korelina; N. P. Zinina (Труды по прикладной ботанике, генетике и селекции, 2018)
The breeding material of oats provided by the breeders of the Moscow Research Institute of Agriculture was assessed on the sites of the Kotlasskoye Federal Enterprise. The article presents the results of the three-year trials (2014-2016) of 57 oats accessions to assess their resistance to loose smut and red-brown leaf spot. According to the results of the tests performed under naturally diseased conditions, two hulled lines (10h2401 and 6h2321) and three hulless ones (38h2273, 11h2267 and 2h2348) were identified as resistant to loose smut, and two lines (10h2401 and 23h2201) as resistant to red-brown leaf spot.